A single dose of anti-IL-1β antibodies prevents Western diet-induced immune activation during early stage collagenase-induced osteoarthritis, but does not ameliorate end-stage pathology. Issue 10 (October 2021) - Kruisbergen, N.N.L.; van Gemert, Y.; Walgreen, B.; Helsen, M.M.A.; Slöetjes, A.W.; Koenders, M.I.; van de Loo, F.A.J.; Roth, J.; Vogl, T.; van der Kraan, P.M.; Blom, A.B.; van den Bosch, M.H.J.; et al.
Summary: Objective: Metabolic dysfunction can cause IL-1β mediated activation of the innate immune system, which could have important implications for the therapeutic efficacy of IL-1β neutralizing drugs as treatment for OA in the context of metabolic syndrome (MetS). In the present study, we investigated whether early treatment with a single dose of IL-1β blocking antibodies could prevent Western diet (WD) induced changes to systemic monocyte populations and their cytokine secretion profile and herewith modulate collagenase induced osteoarthritis (CiOA) pathology. Methods: CiOA was induced in female C57Bl/6 mice fed either a standard diet (SD) or WD and treated with a single dose of either polyclonal anti-IL-1β antibodies or control. Monocyte subsets and granulocytes in bone marrow and blood were analyzed with flow cytometry, and cytokine expression by bone marrow cells was analyzed using qPCR. Synovial cellularity, cartilage damage and osteophyte formation were assessed on histology. Results: WD feeding of C57Bl/6 mice led to increased serum levels of low-density lipoprotein (LDL) and innate immune activation in the form of an increased number of Ly6C high cells in bone marrow and blood and increased cytokine expression of IL-6 and TNF-α by bone marrow cells. The increase in monocyte number and activity was ameliorated by anti-IL-1β treatment. However, anti-IL-1β treatment did not significantly affect synovial lining thickness, cartilage damage and ectopic bone formation during WD feeding. Conclusions: Single-dose systemic anti-IL-1β treatment prevented WD-induced innate immune activation during early stage CiOA in C57Bl/6 mice, but did not ameliorate joint pathology.